PENGENALAN ILMU PENGETAHUAN ALAM MELALUI DEMONSTRASI SEDERHANA - NURDENI NURDENI; FATWA PATIMAH NURSA’ADAH (Faktor Exacta, 2016)
This article focus on the discussion of “instructional chemistry economic-based” Chemistry work is a students’ learning process which is constructed by teachers to develop creative thinking, so it can improve the ability to build a new knowlege and to increase mastering on the material. Hopefully, Instructional chemistry economic-based is expected to increase cognitive, affective and physicomotor, so the teacher’s paradigm about chemistry work is expensive can be eliminated.  Practical work can use the tools and materials in the daily life, such as balloon, citric acid, vegetable oil, eggs, funnel, water, floss, ice, salt, candles, matches, turmeric, bottles, etc.  Keywords: Practical work, Chemistry, Economies Based